Odpowiedź :
a)
6x-18>0
6x>18 |:6
x>3
Odp. Funkcja przyjmuje wartosci dodatnie dla x>3, natomiast wartosci ujemne dla x<3
b)
-3x+1>0
-3x>-1 |:(-3)
x<1/3
Odp. Funkcja przyjmuje wartosci dodatnie dla x<1/3, natomiast wartosci ujemne dla x>1/3
c)
1/2x+20>0
1/2x>-20 |:(1/2)
x>-40
Odp. Funkcja przyjmuje wartosci dodatnie dla x>-40, natomiast wartosci ujemne dla x<-40
6x-18>0
6x>18 |:6
x>3
Odp. Funkcja przyjmuje wartosci dodatnie dla x>3, natomiast wartosci ujemne dla x<3
b)
-3x+1>0
-3x>-1 |:(-3)
x<1/3
Odp. Funkcja przyjmuje wartosci dodatnie dla x<1/3, natomiast wartosci ujemne dla x>1/3
c)
1/2x+20>0
1/2x>-20 |:(1/2)
x>-40
Odp. Funkcja przyjmuje wartosci dodatnie dla x>-40, natomiast wartosci ujemne dla x<-40
a) f(x)>0 <=> x>3
f(x)<0 <=> x<3
b) f(x)>0 <=> x<1/3
f(x)<0 <=> x>1/3
c) f(x)>0 <=> x>-40
f(x)<0 <=> x<-40
f(x)<0 <=> x<3
b) f(x)>0 <=> x<1/3
f(x)<0 <=> x>1/3
c) f(x)>0 <=> x>-40
f(x)<0 <=> x<-40
a)
y =6x - 18
6x - 18 > 0 <=> 6x >18 <=> x> 18 :6 <=> x > 3
y> 0 dla x> 3
y< 0 dla x< 3
b)
y = -3x + 1
-3x +1 > 0 <=> -3x> -1 <-> x < 1/3
y> 0 dla x < 1/3
y<0 dla x > 1/3
c)
y =0,5 x + 20
0,5 x + 20> 0 <=> 0,5x > - 20 <=> x> -40
y> 0 dla x> -40
y< 0 dla x < -40
y =6x - 18
6x - 18 > 0 <=> 6x >18 <=> x> 18 :6 <=> x > 3
y> 0 dla x> 3
y< 0 dla x< 3
b)
y = -3x + 1
-3x +1 > 0 <=> -3x> -1 <-> x < 1/3
y> 0 dla x < 1/3
y<0 dla x > 1/3
c)
y =0,5 x + 20
0,5 x + 20> 0 <=> 0,5x > - 20 <=> x> -40
y> 0 dla x> -40
y< 0 dla x < -40